Pengembangan Model Pembelajaran Heading Dalam Permainan Sepak Takraw - Jenrian Putra Sadimo; Didik Purwanto; Sardiman Sardiman; Andi Saparia; Tesa Alex Suhendra (Universitas Hamzanwadi, 2026)
The teaching of heading techniques in sepak takraw at the university level still faces challenges in the form of monotonous methods, a lack of exercise variety, and the absence of a standardized and proven learning model. This study aims to develop an innovative, structured, and practical heading learning model for Physical Education and Sports Science (PJKR) students at Tadulako University. The research method used was Research and Development (R&D) based on the Borg and Gall model. The research subjects consisted of 1 learning expert, 2 sepak takraw coaching experts, and Physical Education and Sports Science (PJKR) students from the class of 2023, who participated in small-group (n=10) and large-group (n=17) pilot tests. The instrument, a 4-point Likert scale questionnaire, was analyzed using descriptive percentage analysis. The results showed a suitability percentage of 95% (highly suitable) from the learning expert, 68% (suitable) from coach 1, 72% (suitable) from coach 2, 72% (suitable) from the small-group pilot test, and 78% (suitable) from the large-group pilot test. The overall average feasibility of the product reached 77%, falling into the “feasible for use” category. The resulting model consists of six variations of progressive heading drills ranging from low to high difficulty levels. In conclusion, this heading learning model is deemed feasible and can be used as a learning variation to enhance students’ motivation and heading skills.